2021
DOI: 10.1155/2021/6527788
|View full text |Cite
|
Sign up to set email alerts
|

Effects of High Shearing Rates on the Shear Behavior of Saturated Loess Using Ring Shear Tests

Abstract: The shear behavior of saturated loess was examined by performing a series of ring shear tests with different shearing rates. The effects of shearing rates on the shear behavior of saturated loess with different normal stress are presented and discussed. The results showed that peak shear strength and steady-state shear strength were greater when the shearing rate was low and vice versa. Compared with high and low shearing rates, the maximum strength reduction ratios of peak shear strength and steady-state shea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…38 For example, strain-rate dependency experiments on slip belt soils can be performed to obtain their residual strength, which can help to solve the deformation destabilization damage problem of landslides. 39 Ma et al 40 conducted drained tests on saturated loess at different strain rates using a ring shear apparatus and found that the shear strength of the specimen was greater at a lower strain rate. As the strain rate increased, the shear stress caused the soil particles to be crushed and the proportion of clay-grade particles to increase.…”
Section: Introductionmentioning
confidence: 99%
“…38 For example, strain-rate dependency experiments on slip belt soils can be performed to obtain their residual strength, which can help to solve the deformation destabilization damage problem of landslides. 39 Ma et al 40 conducted drained tests on saturated loess at different strain rates using a ring shear apparatus and found that the shear strength of the specimen was greater at a lower strain rate. As the strain rate increased, the shear stress caused the soil particles to be crushed and the proportion of clay-grade particles to increase.…”
Section: Introductionmentioning
confidence: 99%
“…Since landslides often occur at different velocities, the effect of shear rate on residual strength plays an important role in selecting appropriate parameters for designing the countermeasures. So far, the rate effect on the residual strength of various types of soil has been widely investigated (Tika et al, 1996;Skempton, 1985;Li and Aydin, 2013;Scaringi and Di Maio, 2016;Duong et al, 2018;Lian et al, 2018;Xu et al, 2018;Wang and Cong, 2019;Tiwari et al, 2020;Wang et al, 2020;Ma et al, 2021). Some investigations have shown that the rate dependency of residual strength of soil may depend on the mineralogical composition, soil density, normal stress, pore water chemistry, and Atterberg's limit.…”
Section: Introductionmentioning
confidence: 99%